2016
DOI: 10.1055/s-0035-1571196
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 and Type 2 Diabetes Preconception and in Pregnancy: Health Impacts, Influence of Obesity and Lifestyle, and Principles of Management

Abstract: Preexisting diabetes in pregnancy results in increased risks to the mother, fetus, and neonate. Preconception care is vital to reduce risk of miscarriage, congenital malformations, and perinatal mortality. Preconception care should empower women with realistic goal setting, healthy lifestyle, and diabetes self-management skills, to ensure a positive experience of the pregnancy and to reduce diabetes-related distress. In high-risk women without known diabetes, preconception and early antenatal screening is cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…Catalano et al has shown that even women with obesity who gain inadequate weight during pregnancy (<5 kg) have a significantly increased risk of SGA infants . These infants carry the same long‐term metabolic risks as LGA infants . Women should therefore be supported to gain weight during pregnancy according to the 2013 Institute of Medicine guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…Catalano et al has shown that even women with obesity who gain inadequate weight during pregnancy (<5 kg) have a significantly increased risk of SGA infants . These infants carry the same long‐term metabolic risks as LGA infants . Women should therefore be supported to gain weight during pregnancy according to the 2013 Institute of Medicine guidelines .…”
Section: Discussionmentioning
confidence: 99%
“…With the rising prevalence of T2D, decreasing age at onset of the disease and rising maternal age at pregnancy [ 9 ], a significant number of pregnant women have pre-existing T2D [ 10 ]. They are often obese and have high rates of maternal morbidity, including pregnancy-induced hypertension (PIH), preeclampsia and Caesarian delivery [ 11 ]. Infants of diabetic mothers have higher rates of LGA and macrosomia and an increased perinatal morbidity and mortality [ 12 ].…”
Section: Rationale For Metformin In Gestational and Pre-existing Diabmentioning
confidence: 99%
“…While Aboriginal and Torres Strait Islander women tend to have babies at younger ages than non-Indigenous women [ 1 ], risk factors for non-communicable diseases (NCDs) are already common among young Aboriginal and Torres Strait Islander women [ 2 ]. Smoking, high-risk alcohol use, obesity, underweight, poor nutrition and gestational diabetes are risk factors for both adverse pregnancy outcomes and NCDs that are more common among Aboriginal and Torres Strait Islander women than non-Indigenous women [ 1 , 3 – 7 ]. This is consistent with a life expectancy of 10 years less for Aboriginal and Torres Strait Islander women, predominantly due to NCDs [ 5 ].…”
Section: Introductionmentioning
confidence: 99%